The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/aah.10113
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Observations of Dermal Wound Healing in a Free‐Ranging Blacktip Shark from the Southeastern U.S. Atlantic Coast: A Case Report

Abstract: Despite indications that sharks have an exceptional capacity to heal from traumatic injuries, no detailed microscopic observations of integumental wounds have been reported for sharks. This study details the histopathological features of such wounds in a freeranging shark. An adult male Blacktip Shark Carcharhinus limbatus was collected in 2017 during fisheries-independent sampling efforts in the coastal southeastern U.S. Atlantic. The shark had numerous lesions on his head, torso, and left pectoral fin that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Three sharks that were tagged during the study and a fourth shark that was observed during the visual survey had clear propeller injuries on their dorsal fins or the dorsal surface of their bodies. These injuries could be detrimental to individual Great Hammerhead health (Borucinska et al 2020).…”
Section: Fishing Guide Responses To Depredation and Best Practices Re...mentioning
confidence: 99%
“…Three sharks that were tagged during the study and a fourth shark that was observed during the visual survey had clear propeller injuries on their dorsal fins or the dorsal surface of their bodies. These injuries could be detrimental to individual Great Hammerhead health (Borucinska et al 2020).…”
Section: Fishing Guide Responses To Depredation and Best Practices Re...mentioning
confidence: 99%
“…Whether vertebrate limb regeneration is a vestige of ancestral whole-body regeneration, or an evolutionary novelty depends on whether "the entire ancestral line of animals has had a similar regenerative ability" (Slack, 2017). Recent evidence supports this ancestral continuity: tunicates have extensive regenerative abilities, cephalochordates regenerate the tail through a mechanism at least superficially similar to axolotl regeneration (Ferrario et al, 2020), larval jawless fish such as lampreys can regenerate their tails (Bayramov et al, 2018), sharks have recently been shown to regenerate fins (Lu et al, 2013;Alibardi, 2019;2022a;Borucinska et al, 2020;Marconi et al, 2020;Womersley et al, 2021), and of course there are many examples of appendage regeneration throughout the bony fish (Yoshinari and Kawakami, 2011;Nogueira et al, 2016;Darnet et al, 2019).…”
Section: The Evolutionary Origins Of the Vertebrate Blastema Within T...mentioning
confidence: 99%
“…Sharks and cartilaginous fish have only recently been demonstrated to exhibit enhanced muscle, cartilage, CNS and organ regeneration in comparison to amniotes ( Lu et al, 2013 ; Alibardi, 2019 ; Borucinska et al, 2020 ; Marconi et al, 2020 ; Womersley et al, 2021 ; Alibardi, 2022a ). As most of these studies are observational, the molecular basis of these processes remains unexamined, and it is unclear how closely they resemble salamander limb regeneration on the molecular level.…”
Section: An Overview Of Metazoan Regeneration: From Salamander Limbs ...mentioning
confidence: 99%
“…The risk of attaining an injury due to predation (e.g., van den Hoff and Morrice 2008), mating (e.g., Schulte et al 2021), or human actions (e.g., Jakes et al 2018) is prevalent throughout all life stages. In marine habitats, members of Chondrichthyes in the subclass Elasmobranchii (i.e., sharks and rays) seem to withstand trauma (e.g., Borucinska et al 2020; Gardiner and Wiley 2020) and recover from severe, life‐threatening injuries (Towner et al 2012; Womersley et al 2021). Bird (1978) documented extensive tissue healing of three carcharhinid sharks that suffered from deep wounds caused by plastic straps.…”
Section: Introductionmentioning
confidence: 99%